Uso da terapia celular em lesões digitais induzidas em bovinos manejados intensivamente - Noronha Filho, Antônio Dionísio Feitosa (2013)
Digital diseases worries livestock industry and arouse interest in extensionists because of the economic losses and difficult control. Losses come from decrease in productive and reproductive performance and, in some cases, the premature culling of high value breeding animals. Besides these, lameness causes negative impact on animal welfare. Digital diseases assume different characteristics in distinct production systems, requiring specific solutions that fits each farms condition. Innovative treatments have been discussed, but are not always economically viable, however, in last years in Veterinary Medicine has increased the interest on the possibility of applying cell therapy in the treatment of diseases related to the locomotor systems, including digital diseases. In the equine, it has been studied its use in the repair of tendineous, articular and osseous lesions, and the perspective of application in other important diseases like laminitis. Considering the importance of digital diseases, especially laminitis, for cattle, cell therapy can represent an additional option for treatment. This study evaluated the development of digital lesions in cattle intensively managed and its response to the treatment with bone marrow mononuclear cells. Were used 15 animals, male, cross-bred (Bos taurus X Bos indicus), healthy, aging about 12 months and with average weight of151,6 ± 24,65 kg, divided in two groups (GT, n=7, GC, n=8). The study was developed in three stages divided in evaluation moments. On first stage, on second month of confinement, after adjustment of management over concrete floor and feeding of corn silage and concentrate, hooves were trimmed and started evaluation of digital disease wich extended to the tenth month. At this time, were observed digital lesions that developed in the period, their influence over behavior and was conducted radiographic examinations trying to establish relationship between external and internal lesions of digits. After ten months of study all animals had its hooves trimmed and all digital lesions, in decorrence of management, were surgically treated. At this time, started last stage in wich animals received cell therapy. To obtain material needed for the protocol, were harvested samples of bone marrow from animals belonging to treatment group (GT). After this, mononuclear cells were isolated and samples were injected at jugular vein. In the protocol for bone marrow harvest and isolation of mononuclear cells was used Ficoll-Paque. On animals from control group (GC), their lesions were treated during hoof trimming, but all anials were evaluated at twelfth month. To certify the effect of cell therapy, besides clinical examination, identification of possible recidivance or new lesions, were done histological examination for occurrence of hyperemia, hemorrhages or edema on dermis, presence of white blood cells inside or outside vessels and necrosis of basal cells from epidermis, and radiographic examination. On direct inspection were observed expressive occurrence of digital lesions like heel horn erosion, haematoma and erosions of sole and white line disease, however with no difference between groups. Major changes in behavior observed along time were decrease in eating time and increase in times lying down and in leisure. Radiographic evaluation didn´t show signs of distal phalanx rotation suggesting external alterations may not be related to internal alterations. Protocols for bone marrow aspiration and for cell isolation using Ficoll-Paque were effective, resulting in obtainance of mononuclear cells with satisfatory viability. But, since it wasn´t observed significative differences between groups related to digital lesions, histological and radiographical examinations, the reoccurrence and appearance of new lesions after cell therapy cannot be related to this treatment, because seem to be more related to management conditions. It can be concluded that applying of bone marrow derived mononuclear cells at jugular vein didn´t show benefits as auxiliary treatment of digital lesions in cattle. The control of risk factors and site of cell application seem to explain the apparent failure of the therapeutic protocol used.